2012
DOI: 10.1111/j.1365-3016.2012.01313.x
|View full text |Cite
|
Sign up to set email alerts
|

Is it Time to Replace Iron Folate Supplements in Pregnancy with Multiple Micronutrients?

Abstract: Anaemia is one of the most resilient global public health problems and affects a staggering 1.62 billion of the world's population, largely concentrated in Asia and Africa. Anaemia contributes to almost 120 000 maternal deaths globally and indirectly to almost a fifth (18%) of the burden of maternal mortality. Given the widespread prevalence of micronutrient deficiencies in developing countries, supplementation with multiple micronutrients rather than iron folate alone, could be of potential benefit to the mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 48 publications
8
34
0
Order By: Relevance
“…As reported in earlier publications, the included trials were of high quality and the overall quality of evidence for our outcomes were from moderate to high [6,7]. One major concern is the definition of the intervention and control group.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…As reported in earlier publications, the included trials were of high quality and the overall quality of evidence for our outcomes were from moderate to high [6,7]. One major concern is the definition of the intervention and control group.…”
Section: Discussionmentioning
confidence: 68%
“…We identified published studies through October 2011 from PubMed and EMBASE databases using search strategies that have been published elsewhere [6,7]. Additional studies were identified through hand search of references from previous review articles and from personal communications.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the meta-analyses primarily focused on nutrition interventions during pregnancy, the topics of antihelminthics in pregnancy, nutrition education and counseling, household food production, short interpregnancy interval, early age at first childbirth, nutrition before and during pregnancy, and intergenerational influences on child growth and undernutrition were included because of their potential impact on maternal and child health outcomes [10][11][12][13][14][15][16]. We reviewed meta-analyses of the following specific supplementation trials during pregnancy: iron or iron + folic acid (IFA), vitamin A, select B vitamins, vitamin D, n-3 long-chain polyunsaturated fatty acids (n-3 PUFA), iodine, zinc, calcium, multiple micronutrient (MMN), balanced protein-energy, and antihelminthics [10,[17][18][19][20][21][22][23][24][25][26][27]. For all reviews, authors abstracted study data using a standardized Excel-based tool that captured information on 49 potential variables, for example sample size, study design, study context, and estimated effect [9].…”
Section: Methodsmentioning
confidence: 99%
“…Of note, calcium supplementation decreased the risk of preeclampsia, pregnancy-induced hypertension, and maternal mortality/ severe morbidity [24]. Iron or IFA and vitamin A significantly decreased the risk of maternal anemia [17,18], but MMN interventions did not further reduce the risk of anemia compared to IFA [27]. We did not find any evidence of benefit for maternal mortality that was based on fewer trials (n = 5) that examined the effects of vitamin A (RR: 0.86, 95% CI: 0.6-1.24; 3 trials) and MMN interventions (RR: 0.96, 95% CI: 0.64-1.45; 2 trials) [18,25].…”
Section: Nutrition Interventions During Pregnancymentioning
confidence: 97%